The conundrum of ownership in respect of undersea cables and the landing rights in South Africa: understanding the legal regulatory framework - Sindano, John Liwayo (Department of Commercial Law, 2026)
An often-encountered question in practice is how the law is anyway relevant to the issues pertaining to the telecommunications sector. Even more perplexing perhaps is whether or not a legal discourse on the ownership of underwater cables in South Africa or Africa at large is absolutely essential.